Lighting photo workshop - Bucher, Chris. (Wiley Pub., 2007)
Offers advice and instruction on creating sucessful photographs in any lighting situation, including tips on working with natural light, creating effects with shadows, and shooting photographs at night and in low-light.
Chris Bucher.
Keywords: Photography; Lighting; Digital photography